Effect of tofogliflozin on cardiac and vascular endothelial function in patients with type 2 diabetes and heart diseases: A pilot study. Issue 2 (14th August 2019) - Tochiya, Mayu; Makino, Hisashi; Tamanaha, Tamiko; Matsuo, Miki; Hishida, Ai; Koezuka, Ryo; Ohata, Yoko; Tomita, Tsutomu; Son, Choel; Miyamoto, Yoshihiro; Yasuda, Satoshi; Hosoda, Kiminori
Abstract : In this study, we evaluated the effect of treatment with tofogliflozin for 6 months on cardiac and vascular endothelial function in 26 patients with type 2 diabetes and heart diseases. The results suggest that sodium–glucose cotransporter 2 inhibitor might improve left ventricular dilatation and vascular endothelial function in patients with type 2 diabetes. Furthermore, it is suggested that the elevation of ketone bodies induced by sodium–glucose cotransporter 2 inhibitors might contribute to a protective effect in left ventricular diastolic dysfunction. Abstract: Recent studies have shown that sodium–glucose cotransporter 2 inhibitors decrease the risk of heart failure in patients with type 2 diabetes. However, the precise mechanisms of action of these drugs are not well understood. In the present study, we evaluated the effect of treatment with tofogliflozin for 6 months on cardiac and vascular endothelial function in 26 patients with type 2 diabetes and heart diseases. Tofogliflozin treatment significantly decreased left ventricular end‐diastolic dimensions and significantly increased flow‐mediated vasodilation. Although E/e ′ did not significantly change after treatment, the decrease observed in the E/e ′ ratio was significantly correlated with the increase in acetoacetic acid and 3‐hydroxybutyrate levels. These results suggest that sodium–glucose cotransporter 2 inhibitor might improve left ventricular dilatation and vascular endothelial function in patients with type 2 diabetes. Furthermore, it is suggested that the elevation of ketone bodies induced by sodium–glucose cotransporter 2 inhibitors might contribute to a protective effect in left ventricular diastolic dysfunction.